Proteasome (Prosome) Subunit Variations during the Differentiation of Myeloid U937 Cells - Laurent Henry; Ahsene Baz; Marie-Thérèse Château; René Caravano; Klaus Scherrer; Jean Paul Bureau (Analytical Cellular Pathology, 1997)
20S proteasomes (prosomes/multicatalytic proteinase) are protein particles built of 28 subunits in variable composition. We studied the changes in proteasome subunit composition during the differentiation of U937 cells induced by phorbol‐myristate‐acetate or retinoic acid plus 1,25‐dihydroxy‐cholecalciferol by western blot, flow cytometry and immuno‐fluorescence. p25K (C3), p27K (IOTA) and p30/33K (C2) subunits were detected in both the nucleus and cytoplasm of undifferentiated cells. Flow cytometry demonstrated a biphasic decrease in proteasome subunits detection during differentiation induced by RA+VD. PMA caused an early transient decrease in these subunits followed by a return to their control level, except for p30/33K, which remained low. Immuno‐fluorescence also showed differences in the cytolocalization of the subunits, with a particular decrease in antigen labeling in the nucleus of RA+VD‐induced cells, and a scattering in the cytoplasm and a reorganization in the nucleus of PMA‐induced cells. Small amounts of proteasomal proteins were seen on the outer membrane of non‐induced cells; these membrane proteins disappeared when treated with RA+VD, whereas some increased on PMA‐induced cells. The differential changes in the distribution and type of proteasomes in RA+VD and PMA‐induced cells indicate that, possibly, 20S proteasomes may play a role in relation to the mechanisms of differentiation and the inducer used.